The subjectified and subjectifying mind - Han, Min, 1975-; Cunha, Carla (Advances in cultural psychology., 2017)
Putting subjectivity back in psychology and in social sciences is the aim of this volume. Subjectivity is a core psychological dimension but frequently forgotten. Without a full understanding of the uniqueness of each human life our understanding of psychological life fails to reach its aim. This book explores precisely the field of subjectivity, offering the reader different and innovative views on this challenging theme. This book is an asset for all those interested in understanding how the mind operates as a subjectifying process and how this subjectifying mind is simultaneously the product and the content of feeling an unique and unrepeatable subjective life.By bringing together renowned and emergent experts in the field, it provides a fresh new look on the human mind. The reader will find thought-provoking and challenging contributions of 26 different scholars, from 10 countries. It covers a wide range of perspectives and approaches, such as dialogical perspectives, cultural psychology approaches, developmental psychology, feminist perspectives, semiotics, and anthropology.This volume will be very much recommended for all sorts of scholars and students in social and human sciences interested in the human mind and in subjectivity. It will be adequate for different levels of teaching, from undergraduate to master courses. It also meant to be understood for all readers interested in the topic.